Clumped isotope calibration dataset including re-measurement of previous calibration materials and new measurement of Antarctic lacustrine samples and experimentally heated samples (IEDA: EarthChem Library)
Calibration dataset including re-measurement of samples from previous calibration efforts (Kelson et al., 2017; Kluge et al., 2015; Kele et al., 2015; and Bonfacie et al., 2017) as well as new lacustrine Antarctic samples and pressure-cooked samples (total 41 samples). Samples cover 0.5 to 1100 C and include synthetic and natural carbonates from several different origins. Four samples are composed of dolomite, one of aragonite, and 36 of calcite (5 with minor aragonite, 1 with minor goethite).